DETERMINANTS OF ENTREPRENEURS' PERCEPTION ABOUT THE BARRIERS IN DEVELOPING A BUSINESS IN ALBA IULIA - LUCIAN, Marina (Annales Universitatis Apulensis Series Oeconomica, 2016)
the paper deals with the results of a research carried out in 2015 among the entrepreneurs in Alba Iulia. Our hypothesis is that the size, the company's area of activity, the entrepreneurs' age and education, along with other variables, may be determinant factors of how the barriers in developing a business in Alba Iulia are perceived. The study's results may be useful in designing plans of measures and strategies that allow entrepreneurs to overcome the obstacles in their business development, especially by being aware of the fact that some of the perceived barriers are in fact surmountable.